Kinetic behavior of Pt catalyst supported on structured carbon nanofiber bed during hydrogen releasing from decalin. (6th July 2016) - Tuo, Yongxiao; Jiang, Hao; Li, Xing; Shi, Liujie; Yu, Xinhai; Li, Ping
Abstract: It is of great significance to develop practical catalysts with macroscopic sizes for hydrogen releasing. In the present study, two kinds of structured carbon nanofiber (CNF) monoliths synthesized by growing CNFs on the graphite fiber felt in NiC2 H6 and FeCO systems respectively have been used as the supports of Pt catalysts. The catalytic performances have been evaluated in the dehydrogenation of decalin for hydrogen releasing in a tubular flowing reactor. The structure characterization and the reaction kinetic analysis have been conducted upon different supports and catalysts to clarify the main factors influencing the apparent reaction rate. A comparison study has been made with the Pt catalysts supported on activated carbon (AC) pellets. The results show that two structured Pt catalyst beds perform much better at the aspects of both intrinsic catalysis and mass transfer than the catalysts based on AC pellets. The superior catalytic activity of the structured Pt catalysts can be assigned to the smaller Pt particle size and more proper interaction between the metal and the support. The excellent mass diffusion efficiency on both the external and internal sides of fibrous CNF interface can be correlated to the high large-pore porosity and the thin CNF layer in the structured supports, which have been manifested by the calculation of the mass diffusion limitation criteria. Graphical abstract: Highlights: Pt catalysts supported on different structured carbon nanofibers (CNFs) have been synthesized. Decalin dehydrogenation for hydrogen releasing has been conducted over structured catalytic beds. Kinetic behavior of the structured Pt catalysts has been compared with that based on activated carbon pellets. Structured catalysts perform much better at the aspects of both intrinsic activity and mass transfer. The unique microstructure of CNFs and the novel texture of the structured catalyst result in the excellent kinetic behavior.